2018
DOI: 10.1177/0956247817744942
|View full text |Cite
|
Sign up to set email alerts
|

If citizens protest, do water providers listen? Water woes in a Tanzanian town

Abstract: Tanzania's urban citizens are still insufficiently supplied with safe drinking water by their water utilities. However, instead of collectively clamouring for improvements, citizens channel their protests individually to water authorities. This paper aims to shed light on citizens' protest strategies and the responses they elicit from the water authorities. It draws on extensive fieldwork carried out in a Tanzanian town, which revealed four protest strategies employed by citizens: "stay and speak up", "speak u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…When the 'voice' of the community is not taken into account, the service quality may not improve. A study from Tanzania found that dissatisfaction among community members on water service delivery or 'negative feedback' in terms of customers refusing to pay water bills or tampering with meters encouraged decision makers to improve services [38]. Therefore, future WaSH interventions should better integrate the 'voice' of the community, the WaSH committees, and other stakeholders at different stages of the program management: in planning, monitoring, and evaluating interventions.…”
Section: Closing the Knowledge To Action Gapmentioning
confidence: 99%
“…When the 'voice' of the community is not taken into account, the service quality may not improve. A study from Tanzania found that dissatisfaction among community members on water service delivery or 'negative feedback' in terms of customers refusing to pay water bills or tampering with meters encouraged decision makers to improve services [38]. Therefore, future WaSH interventions should better integrate the 'voice' of the community, the WaSH committees, and other stakeholders at different stages of the program management: in planning, monitoring, and evaluating interventions.…”
Section: Closing the Knowledge To Action Gapmentioning
confidence: 99%
“…In the Kalingalinga poor neighbourhood of Lusaka, Zambia, an exhibition of work by local photographers and visual artists which toured internationally, helped to empower the community [146][147][148]. Citizen frustration with basic infrastructure shortages of water, electricity and sanitation pushes them to learn tactics to negotiate improvements [149][150][151][152][153]. Networks of local community actors, for instance, are recycling waste materials into energy briquettes, as alternative cooking energy solutions using locally available technologies [154][155][156].…”
Section: Below the State Level: Local Government Public Awareness And Participation For Meeting Basic Needsmentioning
confidence: 99%
“…The first appearance of PPP in water sector in Tanzania was the setting up of Water kiosks by DAWASCO as a means to supply water to communities that do not have in-house water connection. The kiosks are run by private agents who in return pay rent to DAWASCO [24]. The other aspect of Partnerships involved drilling of boreholes in which both public and private water drilling companies mediate citizens' access to water.…”
Section: Involvement Of Public Private Partnershipmentioning
confidence: 99%